Gating topology of the proton-coupled oligopeptide symporters - CAFFREY, MARTIN; CAFFREY, MARTIN (My University, 2015)
Peptide transport is the main route through which the body absorbs and retains dietary protein and hence plays an important role in human physiology (Steinhardt and Adibi, 1986). The combined action of acid hydrolysis in the stomach and nonspecific peptidases in the small intestine breaks down ingested protein into peptide fragments and free amino acids. The resulting di- and tripeptides are then actively transported across the intestinal brush border membrane by the integral membrane peptide transporter, PepT1 (Fei et al., 1994 and Leibach and Ganapathy, 1996). PepT1 recognizes a diverse range of small peptides and is also responsible for the absorption of many orally administered drugs, including β-lactam antibiotics and a growing number of peptiditic prodrugs (Luckner and Brandsch, 2005, Pieri et al., 2009 and Brandsch, 2009). We do not yet fully understand the mechanism by which PepT1 recognizes and transports molecules into the cell, and this lack of knowledge is hampering the modification of drugs to improve their pharmacokinetic profiles.
PUBLISHED
Cited By :1 Export Date: 19 August 2015
Keywords: Peptide transport; Peptide transport